2013
DOI: 10.1128/iai.01278-12
|View full text |Cite
|
Sign up to set email alerts
|

Influenza-Induced Inflammation Drives Pneumococcal Otitis Media

Abstract: dInfluenza A virus (IAV) predisposes individuals to secondary infections with the bacterium Streptococcus pneumoniae (the pneumococcus). Infections may manifest as pneumonia, sepsis, meningitis, or otitis media (OM). It remains controversial as to whether secondary pneumococcal disease is due to the induction of an aberrant immune response or IAV-induced immunosuppression. Moreover, as the majority of studies have been performed in the context of pneumococcal pneumonia, it remains unclear how far these finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
73
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 34 publications
3
73
0
Order By: Relevance
“…Hemagglutinin (H)-3 subtypes of influenza virus replicate to high titer in the middle ear of mice, and the ensuing inflammatory response promotes replication of S. pneumoniae at this site. 181 This effect is dependent on hemagglutinin subtype, with greater replication of H3 than H1 subtypes in the middle ear, 181 and on anatomic site, with no differences between hemagglutinin subtypes in the nasopharynx. 133 Although influenza in mice is not equivalent to viral infections of the cattle, the concept that virus-induced inflammation can trigger bacterial replication may be informative.…”
Section: Effects Of Predisposing Factors On Bacterial Colonization Ofmentioning
confidence: 99%
“…Hemagglutinin (H)-3 subtypes of influenza virus replicate to high titer in the middle ear of mice, and the ensuing inflammatory response promotes replication of S. pneumoniae at this site. 181 This effect is dependent on hemagglutinin subtype, with greater replication of H3 than H1 subtypes in the middle ear, 181 and on anatomic site, with no differences between hemagglutinin subtypes in the nasopharynx. 133 Although influenza in mice is not equivalent to viral infections of the cattle, the concept that virus-induced inflammation can trigger bacterial replication may be informative.…”
Section: Effects Of Predisposing Factors On Bacterial Colonization Ofmentioning
confidence: 99%
“…Briefly, cell monolayers were infected, and then RNA extraction and DNase treatment were performed as described above. The levels of vRNA and mRNA for the matrix (M), NP, HA, NA, polymerase acidic protein (PA), polymerase B subunit 1 (PB1), PB2, and nonstructural protein (NS) genes were determined via qRT-PCR using SYBR green-based chemistry, as described previously (16). Briefly, cDNA was synthesized using the Omniscript reverse transcriptase kit (Qiagen, USA) according to the manufacturer's instructions with oligo(dT)s (Roche, Australia) for mRNA or Uni12 primer (17) for vRNA.…”
Section: Virus Infection Assaysmentioning
confidence: 99%
“…In clinical cases and experimental models, infection with IAV facilitates the replication of S. pneumoniae in the middle ear (3)(4)(5)(6)(7)(8). Using an infant mouse model of OM (designed to mimic the underdeveloped immune system of children), we have previously demonstrated that the development of pneumococcal OM in coinfected mice was due to the inflammation induced by IAV in the middle ear (3,8). However, the mechanisms by which the host inflammatory response mediates secondary pneumococcal OM remain undefined.…”
mentioning
confidence: 99%